Empowering Community Partnerships in the Creation of Web-Based Financial Reporting for the Serdang Tirta Kencana Village-Owned Enterprise - Endi Putro; Gidion P. Adirinekso; Wahyu Prasetyo (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
Web-Based Financial Reports at Village-Owned Enterprise or Indonesian Badan Usaha Milik Desa (BUMDes) named Serdang Tirta Kencana (STK) is a web-based information system that functions to record financial transactions. The financial reporting system is used by BUMDes STK as a function of accountability for the use of funds, both to the village community and the Village Head. Building a Web-Based Financial Reporting Information System aims to (1) Administrative order. As a form of BUMDes STK's responsibility to the community in carrying out economic tasks. The capital that BUMDes STK has received must have a welfare impact on village communities. For this reason, every expenditure and income received by BUMDes STK must be recorded properly and correctly. (2) Prepare financial reports easily. The Web-Based Financial Report Information System was built in accordance with the needs of BUMDes STK. The involvement of BUMDes STK started from identifying problems in financial reports, analysis, to the information system design. BUMDes STK involvement aims to make the Web-based Financial Report Information System Application become easy to use. Users of the financial report application only need to input transactions; the application will automatically generate the resulting financial reports based on the entered transactions. The output targeted at community service was the Financial Report Information System Application for BUMDes.